The use of Copper Trays Inhausehold in Armenia XIX -XX Centuries - Avetisyan, Mery (History and Culture, 2022)
Summarizing the topic and our research, on the tray, it should be noted that the trays are considered as unique examples of the Armenian culture both from an aesthetic point of view and from that of view of functional significance in everyday life. In addition to the meaning of their daily use, the phenomenon of their ritualism, which was especially characteristic of the traditional life, is very interesting. The rich ornament adorning the trays had a peculiar symbolic meaning and a meaning of the amulet. As for the cultural and everyday value of the trays, which was directly related to the cultural characteristics of the given historical and ethnographic region, we can say that in each period it had different manifestations, the least studied of which is the custom of giving a tray as a gift. So i think it needs a particular research.